To all the bodies I have loved before : the marginalisation of non-homosexual male-male corporeal pleasures in the discourse of gay liberation - Durber, Dean A. (Curtin University, 2004)
In the post-gay liberation era, the body desirous of same-sex sex is presented with the possibility of existing without punishment. Indeed, gay liberation has demanded freedom for this body, insisting that the journey towards enlightened liberation must include a willingness on the part of the body to publicise all of its same-sex sexual desires and pleasures through proud articulation of “I am gay.” This thesis attacks the assumption of freedom assigned within the discourse of gay liberation to both the act of sex and the act of speech. Specifically, I argue against the belief that the body is liberated when it and its pleasures are contained within an identified and identifiable (homo)sexual form.Within the poststructuralist and postmodern contexts, silence has been exposed as a means of repressing the truth. It seeks to deny marginalised bodies the freedom they crave and deserve. Such an interpretation of silence, however, is only one reading among many. I advocate a (re)turn to silence, a (re)casting of it as a mode of resistance to the discipline of the sex-truths established in the culture. In challenging the truths of “man” and “sex” through the construction of a Body without Sex (BwS), I dispute the reality of the homosexual type. The premise of this thesis is that the silence of a BwS offers a space in which the male-d body that engages in same-sex sexualised contact is able to resist the culture’s dictate to be a homosexual. A silencing of anatomical sex and the act of sex disrupts compulsory homosexualisation.This thesis concludes with an application of the concept of a BwS to three male-male relationships in which the participants might experience mutual desires and/or corporeal pleasures. Here, with anticipated controversy, intimate unions between men and boys, “mates” and brothers are removed from the framework of compulsory sexualisation through which the culture demands they must be read. The intensity of the culture’s focus on anatomical sex and the act of sex contain such relationships and the bodies involved within the discipline of the sexual. A BwS aims to resist such discipline through its desire to encourage the body and its pleasures to become other than signifiers of sexual truths.